STUDI PERBANDINGAN KOMPOS DARI DAUN TUMBUHAN DENGAN C/N RASIO BERBEDA TERHADAP ADSORPSI LOGAM BERAT TIMAH HITAM (PB) PADA MEDIA BUDIDAYA IKAN - EVA PRASETIYONO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
Lead (Pb) is non-essential heavy metal that is toxic to cultured fishes. Culture media containing Pb lead to health impacts on cultured fishes or even death. Compost is a material that can be used to adsorb Pb due to its humic acid and fulvic acid content. Compost with a C I N ratio of different raw materials will lead to different content of substances. This study aims to compare the leafs of gamal and Api-api used as raw material to produce the compost and its properties to adsorb Pb in fish culture media. The experiment design used a completely randomized design to determine the best level of gamal leaves and Api-api leaves compost, then followed by multiple comparison test to find the best type of compost to adsorb the Pb. The results showed that the best type of compost to adsorb the Pb in cultivation media was gamal leaf compost at 9 g/1. Water treatment with all kinds of compost and its level, low Pb content in fish meat, the survival rate and the growth, except the leaf compost gamal level of 5 g/1.